(untitled) (Research, Society and Development, 2020)
This article aims to analyze articles from the CAPES and SciELO directories for the period from 2015 to 2019, which address the issue of schooling adolescents in conflict with the law and school violence. Such a study consists of a review of the literature with a quantitative and qualitative approach. The descriptors used were “adolescents in conflict with the law”, “school violence”, “juvenile delinquency”, “teachers”, “students”, “socio-educational measures” and “bullying”. Inclusion criteria were publications in the form of free articles, without language specification, with search for descriptors contained in subject or title. Publications that did not meet the inclusion criteria were excluded. After mining at CAPES and SciELO sources, 09 studies were selected. After the categorization process, the following categories and frequency were obtained: School (f = 13), adolescence (f = 09) and socio-education (f = 08). A large portion of the selected works concluded that the school presents many obstacles to the schooling of adolescent offenders. Among the most frequent problems found in the school environment, related to the schooling of adolescent offenders are: resistance of the school unit to enroll, age-grade distortion, school dropout, high repetition rate, low education, low school bond caused by prejudice suffered, educational practices that do not meet the needs of adolescents and compromised interpersonal relationships; the latter contributes to bringing adolescents closer to delinquent practices. In view of this, it is concluded that the school needs to review its pedagogical strategies aimed at schooling adolescents in conflict with the law.